(untitled) (Global Journals of Research in Engineering, 2012)
Mathematical modeling and simulation of an experimental study was performed using an array of solar panels to power three non-asbestos diaphragm type electrochemical cells whose anodes consisted of carbon rods and cathodes made up of stainless steel plate for the electrolysis of a 25 % w/w sodium chloride solution, with the aim of producing caustic soda. The non-asbestos diaphragms served to hinder the formation of unwanted substances as well as permit reasonable production of the desired products. The three non-asbestos diaphragm cells exhibited various characteristic performances, which is a reflection of their design, fabrication, composition, intensity of the sun on any particular day, the length of time the panels were exposed to sunlight and operational parameters. The non-asbestos diaphragm D3 with composition of 60 % w/w Portland cement, 20 % w/w silica and 20 % w/w polyvinyl chloride (PVC) indicated the highest yield of caustic soda per d.c Watt with specific electrical energy supplied. The simulated values predicted the operation closely as the maximum positive and negative deviations of all modeled from experimental values are between +0.07 and #x2013; 0.06 respectively. The research served as an encouraging inquisitive foundation into the possibility of producing caustic soda directly from solar powered electrolytic diaphragm cells with the aim of designing better cells as well as investigating key factors that affects cell performance in view of present conventional modes of electrochemical production.